COMPARATIVE STUDY FOR USING OF SUB MUCOSA OF SMALL INTESTINE IN HEALING OF CLEAN AND INFECTED AVULSION WOUNDS - AL-FALAHI, N. H. (The Iraqi Journal of Veterinary Medicine, 2009)
This study was done on 29 mature rabbits to observe the effect of sub mucosa of small intestine of sheep inthe healing of avulsion wound in rabbits, animals divided to three equal groups:First group: The avulsion wound in the thigh region was left without treatment, just covering with bandage andconsidered as a control group.Second group: Treatment of clean avulsion wound in the thigh region was done by covering it with sub mucosaof small intestine which previously prepared.Third group: Treatment of infected avulsion wound in the thigh region was done by covering it with sub mucosaof small intestine which previously prepared.The results of this study show that the sub mucosas of small intestine have the ability to enhance healing of thewound with little formation of scar tissue.The macroscopic finding show the faster in approximation of wound edges in groups two and three in the secondweek and with little formation of granulation and the wound site be similar to normal skin in the third week ascompared with control group in which the healing occur by formation of scar tissue observed in the third weekand continue to the forth week, while The histopathological finding show faster in organization of granulationtissue in the second week in groups two and three and the tissue appeared similar to normal skin in the third week,while in control group show increase in formation of granulation tissue which continue until the third week